2022
DOI: 10.1002/anie.202211345
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Reactivity of a Fleeting NiIII Bisphenoxyl Diradical Species

Abstract: Cytochrome P450s and Galactose Oxidases exploit redox active ligands to form reactive high valent intermediates for oxidation reactions. This strategy works well for the late 3d metals where accessing high valent states is rather challenging. Herein, we report the oxidation of Ni II (salenwith mCPBA (meta-chloroperoxybenzoic acid) to form a fleeting Ni III bisphenoxyl diradical species, in CH 3 CN and CH 2 Cl 2 at À 40 °C. Electrochemical and spectroscopic analyses using UV/Vis, EPR, and resonance Raman spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…[35] The significant background reaction due to excess oxidant constraints the quantitative analysis of the oxidized product, while for the quantitative purpose, APCI mass spectrometry data has been recorded (Figures S22 and S23). [37,38] As monitored by UV/Vis spectroscopy, the rate of consumption of 1 a/2 a scales linearly with substrate concentration, suggesting that even in the presence of abundant mCPBA, 1 a/2 a is involved in their oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…[35] The significant background reaction due to excess oxidant constraints the quantitative analysis of the oxidized product, while for the quantitative purpose, APCI mass spectrometry data has been recorded (Figures S22 and S23). [37,38] As monitored by UV/Vis spectroscopy, the rate of consumption of 1 a/2 a scales linearly with substrate concentration, suggesting that even in the presence of abundant mCPBA, 1 a/2 a is involved in their oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…As for their physical description, the resulting metal complexes were all air-stable brown solids. While complexes 3, 5-7, 9, 10 and 12-14 were synthesized for the first time in the context of the current study, 1, 2, 4, 8 and 11 had been synthesized previously [20,[23][24][25][26].…”
Section: Synthesis Of Salen Complexesmentioning
confidence: 95%
“…The research group led by Klein reported studies devoted to the realization of an unprecedented high valent Ni III bisphenoxyl diradical species [20]. Moreover, Ni(II) salen complexes were used as highly active Ni catalysts for the reductive amination of ketones by ammonia [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…aminium radical cation [N(C 6 H 3 Br 2 ) 3 * ] + to form [1 II -L ** ]. [15] Very recently, we reported the action of excess of mCPBA on 1 leading to the formation of Ni(III) bisphenoxyl diradical species, [1 III -L ** ] (Scheme 1a) both in CH 3 CN and CH 2 Cl 2 at 233 K. [16] It has been demonstrated in the literature that the site of oxidation from metal to the ligand (i. e., [1 II -L * ] and [1 III -L]) can be shuffled depending upon the conditions employed. [13] In the present study, we examined the conditions that cause the shift in equilibria in [1 III -L ** ].…”
Section: Introductionmentioning
confidence: 99%